Microstructural constraints on the mechanisms of the transformation to reidite in naturally shocked zircon - Erickson, T.; Pearce, M.; Reddy, S.; Timms, Nicholas; Cavosie, Aaron; Bourdet, J.; Rickard, W.; Nemchin, A. (Springer, 2017)
Zircon (ZrSiO4) is used to study impact structures because it responds to shock loading and unloading in unique, crystallographically controlled manners. One such phenomenon is the transformation of zircon to the high-pressure polymorph, reidite. This study quantifies the geometric and crystallographic orientation relationships between these two phases using naturally shocked zircon grains. Reidite has been characterized in 32 shocked zircon grains (shocked to stages II and III) using a combination of electron backscatter diffraction (EBSD) and focused ion beam cross-sectional imaging techniques. The zircon-bearing clasts were obtained from within suevite breccia from the Nördlingen 1973 borehole, close to the center of the 14.4 Ma Ries impact crater, in Bavaria, Germany. We have determined that multiple sets (up to 4) of reidite lamellae can form in a variety of non-rational habit planes within the parent zircon. However, EBSD mapping demonstrates that all occurrences of lamellar reidite have a consistent interphase misorientation relationship with the host zircon that is characterized by an approximate alignment of a {100}zircon with a {112}reidite and alignment of a {112}zircon with a conjugate {112}reidite. Given the tetragonal symmetry of zircon and reidite, we predict that there are eight possible variants of this interphase relationship for reidite transformation within a single zircon grain.Furthermore, laser Raman mapping of one reidite-bearing grain shows that moderate metamictization can inhibit reidite formation, thereby highlighting that the transformation is controlled by zircon crystallinity. In addition to lamellar reidite, submicrometer-scale granules of reidite were observed in one zircon. The majority of reidite granules have a topotaxial alignment that is similar to the lamellar reidite, with some additional orientation dispersion. We confirm that lamellar reidite likely forms via a deviatoric transformation mechanism in highly crystalline zircon, whereas granular reidite forms via a reconstructive transformation from low-crystallinity ZrSiO4 within the reidite stability field. The results of this study further refine the formation mechanisms and conditions of reidite transformation in naturally shocked zircon.